2018
DOI: 10.1016/j.coal.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Structure and thermal history of the Wełnowiec dump, Poland: A municipal dump rehabilitated with coal waste

Abstract: The Wełnowiec municipal dump, Katowice, Poland, rehabilitated with coal waste, is self-heating and igniting. This paper presents a novel application of the use of electrical-and resistivity geophysical methods in the investigation of burning coal waste to help explain why the heating occurred. Geoelectrical methods allowed the internal structure of the dump to be revealed, and the municipal wastes and their rehabilitation cover containing coal waste to be differentiated. Instead of a planned 2.2-m-thick multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Apart from the initial composition, a signi cant factor affecting the elemental composition of coal waste is weathering and self-heating. The wide occurrence of self-heating in the LSCB and USCB and its impact on coal waste and on the environment has been described earlier (e.g., Ciesielczuk et al 2014;Misz-Kennan et al 2013;Misz-Kennan and Fabiańska 2011;Nádudvari and Fabiańska 2016;Pierwoła et al 2018). In this study, it is assumed that the elements in the water come exclusively from the leaching of coal waste.…”
Section: Origin Of Inorganic Constituents Of Coal-waste Dump Watermentioning
confidence: 84%
See 2 more Smart Citations
“…Apart from the initial composition, a signi cant factor affecting the elemental composition of coal waste is weathering and self-heating. The wide occurrence of self-heating in the LSCB and USCB and its impact on coal waste and on the environment has been described earlier (e.g., Ciesielczuk et al 2014;Misz-Kennan et al 2013;Misz-Kennan and Fabiańska 2011;Nádudvari and Fabiańska 2016;Pierwoła et al 2018). In this study, it is assumed that the elements in the water come exclusively from the leaching of coal waste.…”
Section: Origin Of Inorganic Constituents Of Coal-waste Dump Watermentioning
confidence: 84%
“…On the basis of recent research on the chemical-and mineralogical composition of Upper Silesia waste rocks (Ciesielczuk et al 2014) and on attempts to leach elements from Upper Silesian coal waste (Pierwoła et al, 2018), it can be concluded that elements in waters were leached from rocks and minerals transformed as a result of hypergenesis or dump res. Elements such as Mg, K, Ca, Na, Mn, Fe, Cu, Cd, Pb, and Co occur in coal waste in concentrations ranging from 12-98600 mg/kg.…”
Section: Correlations Between Trace Metals and Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous descriptions from coal basins worldwide of the behaviour during combustion of mainand trace elements in coal (e.g., Swaine 1990;Querol et al 1995;Pusz et al 1997;Baruah et al 2003;Xu et al 2003;Ketris 2002, 2015;Lewińska-Preis et al 2009;Dai et al 2012Dai et al , 2014Kolker 2012;Hower et al 2016). Due to much higher mineral contents, the mobility of trace elements in coal waste is expected to differ significantly from that in coal (Li et al 2011;Zhou et al 2014;Pierwoła et al 2018). However, there are relatively limited data about the behaviour of elements in coal waste during self-heating; some exceptions are Guo (2018), Kruszewski (2019a, b), Nowak et al (2017), Sokol et al (2005), and Zhao et al (2008).…”
Section: Coal Waste and Coal-waste Dump Watersmentioning
confidence: 99%
“…Even less is known about the migration of these elements into soil and surface waters. Some leaching tests (e.g., Huggins et al 2011;Pierwoła et al 2018;Yang et al 2016 andZhang et al 2015) and research on gangue environmental impact (Li et al 2011) indicate that many factors such as pH, type of mineral matrix, mode of element occurrence (water-leachable, ion-exchangeable, organic-bound, carbonate-bound, silicate-bound, sulfidebound), associated elements or method of leaching can affect element mobility (Guo 2018).…”
Section: Coal Waste and Coal-waste Dump Watersmentioning
confidence: 99%